[PP.23.20] PREVALENCE AND SEVERITY OF ERECTILE DYSFUNCTION IN PATIENTS WITH RESISTANT HYPERTENSION. (September 2016) - Boutari, C.; Imprialos, K.P.; Stavropoulos, K.; Kokkinos, P.; Pittaras, A.; Faselis, C.; Petidis, K.; Deligkaris, P.; Stavropoulos, N.; Athyros, V.; Karagiannis, A.; Doumas, M.
Abstract : Objective: Erectile dysfunction is usually of vascular origin and is therefore common in patients with essential hypertension. The prevalence of erectile dysfunction in resistant hypertension has yet to be evaluated. The objective of our study was to estimate the prevalence and severity of erectile dysfunction in male patients with resistant hypertension. Design and method: 124 consecutive male patients with resistant hypertension evaluated in our department's hypertension outpatient clinic were included in our study. Resistant hypertension was defined according to the guidelines as blood pressure > 140/90 mmHg, despite the administration of at least three antihypertensive medications in maximum tolerated dose, including a diuretic. Erectile dysfunction was estimated using the International Index of Erectile Function (IIEF) and a score below 26 was considered indicative of erectile dysfunction. Results: Only 5 patients had been asked whether they presented erectile problems and none of them had been requested to fill a relevant questionnaire. Erectile dysfunction was observed in 83 out of 124 patients of our study (66.9%). Erectile dysfunction was assessed as severe or moderate in the majority of our patients (61/83, 73.5%), whereas mild dysfunction was found in the remaining patients (22/63, 26.5%). Conclusions: Erectile dysfunction is particularly common among patients with resistant hypertension but unfortunately remains under-diagnosed in everyday clinical practice. Continuing medical education is essential for the timely diagnosis and treatment of erectile dysfunction in order to improve the patients' and their sexual partners' quality of life.